Javanese Varieties in Pringsewu Regency and Their Origins - Suprayogi Suprayogi (TEKNOSASTIK, 2019)
It has been an interesting discussion on how certain language is spoken in the area far from its center. This paper is aimed at describing the Javanese language varieties in Pringsewu regency of Lampung province, locating the area where these varieties are spoken, and revealing the history why these varieties appear in the areas. By employing dialectology study using isogloss bundles and dialectometry, it was found that in the 18 Javanese observation locations (OL), the Javanese varieties are mostly indicated by both lexical and sound variation, and these varieties are classified in less than 30% lexical difference.  There are some areas using Banyumas dialect with its distinctive features and also varieties that reflect standard Javanese. The Javanese varieties in this area are spoken as the first language by the informants. The varieties are derived from the migrants coming several parts in Java Island with different periods and motifs of arrival.